1996
DOI: 10.1161/01.res.79.4.821
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle α v β 3 Integrin Mediates Arteriolar Vasodilation in Response to RGD Peptides

Abstract: Arteriolar vasodilation and the resultant increase in blood flow are characteristic vascular responses to tissue injury. The dilatory mediators signaling these responses are incompletely understood. We show that integrin-binding peptides containing the Arg-Gly-Asp (RGD) tripeptide sequence cause immediate and, in some instances, sustained vasodilation when applied to isolated rat cremaster arterioles. The vasodilation is dependent on interaction of the soluble RGD sequence with the alpha v beta 3 integrin expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 28 publications
4
151
1
2
Order By: Relevance
“…Although many studies indicate that synthetic RGD-containing peptides inhibit angiogenesis and tumor growth, our findings provide the first evidence that macrophages may generate and release an RGDKGE-containing collagen epitope that may exhibit pro-angiogenic activity. Importantly, previous studies have suggested that certain RGD peptides can activate ␣v␤3 (58,59) and may enhance vascular permeability (45,57), which might lead to release of inflammatory factors, which in turn may contribute to the formation of new blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies indicate that synthetic RGD-containing peptides inhibit angiogenesis and tumor growth, our findings provide the first evidence that macrophages may generate and release an RGDKGE-containing collagen epitope that may exhibit pro-angiogenic activity. Importantly, previous studies have suggested that certain RGD peptides can activate ␣v␤3 (58,59) and may enhance vascular permeability (45,57), which might lead to release of inflammatory factors, which in turn may contribute to the formation of new blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of isolated arterioles for study has been previously described in detail (20). In brief, male SpragueDawley rats (180-300 g) were anesthetized with pentobarbital sodium (100 mg/kg i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…In the isolated arteriole preparation, GRGDNP, GRGDSP, and a cyclic RGD peptide (GPenGRGDSPCA where Pen ϭ penicillamine; Gibco BRL) induce concentration-dependent arteriolar dilation with the cyclic peptide showing greater potency consistent with its predominant ␣ v ␤ 3 -binding properties (20). The purpose of these experiments was to determine if the role of ␣ 5 ␤ 1 would be made evident after blockade of ␤ 3 integrin function.…”
Section: Rgd Peptides Induce Vasoconstriction After ␤ 3 Integrin Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been provided in support of a role for integrins in the myogenic response, 22 which was found to be suppressed by integrin-specific peptides and blocking antibodies. 20,21,23 Smooth muscle integrins are located in membrane-associated dense plaques, structural analogs of focal adhesions of cultured cells. 24 Integrin stimulation (clustering) induces tyrosine phosphorylation and activation of focal adhesion kinase (FAK) and Src family tyrosine kinases, and increased tyrosine phosphorylation is associated with the myogenic response.…”
Section: The Mechanosensormentioning
confidence: 99%